2023
DOI: 10.2147/jmdh.s403700
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Independent-Comorbidity Groups in Senior COVID-19 Patients Reveal Low Fatality Associated with Standard Care and Low-Dose Hydroxychloroquine over Antivirals

Abstract: The lack of feasible therapies and comorbidities aggravate the COVID-19 case-fatality rate (CFR). However, reports examining CFR associations with diabetes, concomitant cardiovascular diseases, chronic kidney disease, and chronic liver disease (CLD) are limited. More studies assessing hydroxychloroquine (Hcq) and antivirals are needed. Purpose: To examine associations of COVID-19 CFR in comorbid patient groups each with single comorbidities and after treatment with Hcq, favipiravir, and dexamethasone (Dex), ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 109 publications
1
6
0
Order By: Relevance
“…In conclusion, we agree that there is a correlation of comorbidities in Covid-19 patients where diabetes is the highest comorbidity and the relationship with CFR is very significant, 1 but close monitoring must be carried out, especially in patients with underlying diseases such as kidney or heart disease. 3 In addition, standard therapy is recommended for the category of patients who are not severe and for groups with severe symptoms, it is recommended that antiviral combination therapy such as HCQ + ribavirin have a role in increasing clinical recovery in patients with Covid-19 and reducing the period of morbidity.…”
Section: Dear Editorsupporting
confidence: 60%
See 3 more Smart Citations
“…In conclusion, we agree that there is a correlation of comorbidities in Covid-19 patients where diabetes is the highest comorbidity and the relationship with CFR is very significant, 1 but close monitoring must be carried out, especially in patients with underlying diseases such as kidney or heart disease. 3 In addition, standard therapy is recommended for the category of patients who are not severe and for groups with severe symptoms, it is recommended that antiviral combination therapy such as HCQ + ribavirin have a role in increasing clinical recovery in patients with Covid-19 and reducing the period of morbidity.…”
Section: Dear Editorsupporting
confidence: 60%
“…We have read the paper by Kamaleldin B Said et al on Profiles of Independent-Comorbidity Groups in Senior Covid-19 Patients Reveal Low Fatality Associated with Standard Care and Low-Dose Hydroxychloroquine over Antivirals. 1 We congratulate the authors for providing the latest information regarding the relationship between comorbid factors and the therapy given to the case-fatality rate (CFR) of Covid-19 patients. This research will give us an overview regarding the best therapeutic options that are appropriate for Covid-19 patients.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is counted among the main risk factors, the results of studies to date are somewhat mixed. Some comparative studies showed no direct correlation between diabetes and mortality for COVID-19, but rather with the variety of disorders that diabetes causes in the organism [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%